Yasal Düzenlemeler Işığında Hava Hukukunun Tarihsel Gelişimi ve İlk Türk Hava Hukuku Metni - (:unkn) unknown (My University, 2017)
Hava hukukunun gelişimi, her hukuk dalında olduğu gibi yasal düzenlemeler ile olmaktadır. Tüm dünyada devletlerin havacılığa yaklaşımı ilk aşamada yasaklama yönünde olmuştur. Sonrasında havacılık faaliyetlerine izin verilmiş ve kimi devletler havacılık faaliyetlerinde etkin olmaya başlamıştır. Bu doğrultuda, Türk sivil havacılığına ilişkin ilk faaliyetler ve bu faaliyetlere yönelik yasal düzenlemeler çalışmamızda incelenecektir.

The development of air law is in accordance with legal regulations as it is in every branch of law. In first stage, states around the world forbid aviation activity. After that, aviation activities were allowed and some states have begun to be active in aviation activities. Activities related to Turkish civil aviation and legal regulations for these activities will be explained.Keyords: Administrative law, Air law, Civil aviation.
Historical Development of Air Law in the Light of Legal Regulations and the First Turkish Air Law Text
Keywords: Hukuk